Branding dan Pemanfaatan Media Sosial dalam Meningkatkan Penjualan Nasi Uduk Ayam Geprek ECO - Aurellius Krisna Putra; Andreas Candra; Claudius Kristian Hery; Illona Hartanto; Jennifer Huang; Jemmy Jemmy; Lauren MI. Aidelin; Santi Rimadias (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2024)
The growth of the digital era has brought changes in the operations of Micro, Small, and Medium Enterprises (MSMEs). The key to the success of MSMEs today can be supported by branding and the use of social media. The use of social media is still not optimal. However, business actors already have a fairly inherent branding, namely ECO which means "Delicious". The writer here is a facilitator to bridge business actors to enter the digital world and help market it through social media. In addition, the author also physically assisted in the form of making a logo, creating a new menu, creating social media accounts (Instagram), creating video content, giving banners and giving new aprons to help increase sales and cleanliness of Nasi Uduk Ayam Geprek ECO